Can Pictograms Help Older Adults to Assess Their Own Level of Functional Capacity? Using Human Centered Design Methods to Develop and Validate Pictograms for the Functional Assessment of Activities of Daily Living - Tierney, Lauren; Murmann, Maya; Manuel, Douglas G.; Trudel, Chantal; Bennett, Carol; Sveistrup, Heidi; Hsu, Amy T. (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Despite the potential value of image-based tools, and the fact that self-reported functional status has been shown to be reliable and have predictive validity, few visual-based assessment tools, or mixed-modality tools incorporating pictograms, for function exist. The main objectives were to 1) Explore the potential benefit of visual based tools (i.e., pictograms) for the use of self-assessment tools; 2) Present methods for co-designing clinical pictograms with older adults; and, 3) Discuss the prospect of using pictograms for self-assessment tools and discuss the prospect of using pictograms for self-assessment tools. From an accessibility perspective, the use of visuals may be particularly beneficial in individuals, like older adults, that have accessibility needs, such as cognitive impairment. The development of pictograms to measure a concept requires careful consideration to ensure the graphical representational aligns with the intended meaning, which is context dependent. The development of pictograms for self-administered functional assessments tools may increase the accessibility and ease of use of self-assessment tools for older adults, given the limitations of current text-based tools.